Stimulation TcPO2 Testing Improves Diagnosis of Peripheral Arterial Disease in Patients With Diabetic Foot - Fejfarová, Vladimíra; Matuška, Jiří; Jude, Edward; Piťhová, Pavlína; Flekač, Milan; Roztočil, Karel; Wosková, Veronika; Dubský, Michal; Jirkovská, Alexandra; Bém, Robert; Husáková, Jitka; Lánská, Věra (Frontiers in Endocrinology, 2021)
Background: All diagnostic procedures of peripheral arterial disease (PAD) in diabetic foot (DF) are complicated due to diabetes mellitus and its late complications. The aim of our study is to enhance diagnosis of PAD using a novel transcutaneous oximetry (TcPO2) stimulation test. Methods:The study comprised patients with mild-to-moderate PAD(WIfI–I 1 or 2) and baseline TcPO2 values of 30-50 mmHg.TcPO2 was measured across 107 different angiosomes. Stimulation examination involved a modification of the Ratschow test. All patients underwent PAD assessment (systolic blood pressures (SBP), toe pressures(TP), the ankle-brachial indexes (ABI) and toe-brachial indexes (TBI), duplex ultrasound of circulation). Angiosomes were divided into two groups based on ultrasound findings: group M(n=60) with monophasic flow; group T(n=47) with triphasic flow. Large vessel parameters and TcPO2 at rest and after exercise (minimal TcPO2, changes in TcPO2 from baseline (Δ,%), TcPO2 recovery time) measured during the stimulation test were compared between study groups. Results: During the TcPO2 stimulation exercise test, group M exhibited significantly lower minimal TcPO2 (26.2±11.1 vs. 31.4±9.4 mmHg; p<0.01), greater Δ and percentage decreases from resting TcPO2 (p=0.014 and p=0.007, respectively) and longer TcPO2 recovery times (446±134 vs. 370±81ms;p=0.0005) compared to group T. SBPs, TPs and indexes were significantly lower in group M compared to group T. Sensitivity and specificity of TcPO2 stimulation parameters during PAD detection increased significantly to the level of SBP, ABI, TP and TBI. Conclusion: Compared to resting TcPO2, TcPO2 measured during stimulation improves detection of latent forms of PAD and restenosis/obliterations of previously treated arteries in diabetic foot patients.